Advancing green skills in Indonesian Higher Education: roles, barriers, and transformative strategies - Carolus Borromeus Mulyatno; Rian Antony (CV. Literasi Indonesia, 2026)
This article aims to provide a critical analysis of green skills development in higher education institutions (HEIs) in Indonesia. This critical analysis is conducted because HEIs are still experiencing obstacles in developing students' green skills. It is important to recognize that developing students' green skills is an indispensable prerequisite for obtaining new qualifications that are crucial in this era. The purpose of this article is to comprehensively examine the roles, challenges, and strategies of HEIs in Indonesia in developing students' green skills. This study uses a qualitative research methodology, focusing on exploring the perspectives of seven informants through in-depth interviews. The informants were selected through non-probability sampling, a method carefully applied to ensure the collection of high-quality information relevant to the research objectives. The study's findings indicate that HEIs play a crucial role in developing students' green skills through curriculum transformation, contextual learning, and collaboration with the workplace. Furthermore, these findings also contribute to the growing literature on green skills in higher education and offer practical recommendations for strengthening sustainability-oriented policies and practices in Indonesian universities. However, challenges such as limited educator capacity, lack of technical guidance, and lack of collaboration with the workplace persist.